2011
DOI: 10.1021/tx200333g
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochic Acid I Metabolism in the Isolated Perfused Rat Kidney

Abstract: Aristolochic acids are natural nitro-compounds found globally in the plant genus Aristolochia that have been implicated in the severe illness in humans termed aristolochic acid nephropathy (AAN). Aristolochic acids undergo nitroreduction, among other metabolic reactions, and active intermediates arise that are carcinogenic. Previous experiments with rats showed that aristolochic acid I (AA-I), after oral administration or injection, is subjected to detoxication reactions to give aristolochic acid Ia, aristolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
(148 reference statements)
1
17
0
Order By: Relevance
“…With respect to the dosage required to elicit tubular damage, rats are the least sensitive rodent species (21). This has been attributed, in part, to the proficiency of isolated rat kidneys perfused with AA-I in producing the primary detoxication products of AA-I, namely, AA-Ia and its O6-conjugates (25). Murine kidneys lack this detoxication pathway.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the dosage required to elicit tubular damage, rats are the least sensitive rodent species (21). This has been attributed, in part, to the proficiency of isolated rat kidneys perfused with AA-I in producing the primary detoxication products of AA-I, namely, AA-Ia and its O6-conjugates (25). Murine kidneys lack this detoxication pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Priestap and his colleagues investigated the metabolism process of AA-I in the isolated perfusing rat kidney. 4 They found that AA-I distributed rapidly and extensively in kidney tissues by uptake from the peritubular capillaries and the tubules. And, the filtered AA-I was reabsorbed at the tubules, whereas its metabolites were secreted.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, an isolated organ is the sole contributor to changes in metabolite concentrations, which allows these changes to be attributed to organ-specific influences. This can be exploited to study the effects of certain interventions in basic metabolic pathways 132 or the metabolism of a target compound 133,134 . Additionally, the ease of in- and outflow sampling allows for metabolic flux analysis over the organ and the evaluation of metabolic pathways over time and between groups 33,135 .…”
Section: Applicationsmentioning
confidence: 99%